On the Assimilation of New Information on Asset Prices - Milionis , Alexandros E. (An Overview on Business, Management and Economics Research Vol. 5, 2023)
A simple linear model describing a mechanism for the assimilation of new information on traded assets’ prices is introduced. The model is useful in its own right, as it provides a simplified, yet credible, quantitative description of the reality. Further, the model is used as a tool for a theoretical study of market efficiency testing. This is obtained by modelling certain market conditions under which new information is released and assimilated in asset prices on the one hand, and, on the other hand, by recording what established econometric testing approaches conclude, about the hypothesis of market efficiency. Amongst others it is argued that contrary to the general belief, theoretically a random walk in asset prices, under certain conditions, could be associated with inefficient markets. Furthermore, an enhancement of the battery of statistical tests for market efficiency is proposed by the potential application of specific forms of the suggested linear dynamic model and the possible advantages over the existing techniques are explained. Last but not least, although the conventional terminology of market efficiency classification is used, the proposed model for the assimilation of new information in asset prices is more conducive to a categorical rather than the existing ordinal classification of market efficiency.